When saving is not enough: The wealth decumulation decision in retirement - Pascal Kieren; Martin Weber (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
In this study, we investigate the wealth decumulation decision from the perspective of a retiree who is averse to the prospect of fully annuitizing her accumulated savings. We field a large online survey of hypothetical product choices for phased drawdown offerings and annuities. While the demand for annuities remains low in our sample, we find significant demand for phased withdrawal products with equity-based asset allocations and flexible payout structures. Consistent with the product choice, the most important self-reported considerations for the wealth decumulation decision are low default risk in the products they purchase, the size of the withdrawal rates, and flexibility in the timing of their withdrawal. As determinants of the decision of how much wealth individuals are willing to draw down, we identify consumers' attitudes towards future economic conditions, the extent to which they are protected against longevity risk, and their desire to leave bequests. Policy implications are discussed.
urn:nbn:de:hebis:30:3-515959
Keywords: D14; G2; H55; J14; J26; 330; retirement planning; phased withdrawal accounts; annuity puzzle